Eksplorasi Bakteri Endofit Terhadap Cendawan Pestalotiopsis microspora Penyebab Penyakit Gugur Daun Pada Tanaman Karet (Hevea brasiliensis Muell. Arg.) - Vazza Navtra Tylova; Syamsul Bahri; Boy Riza Juanda; Alchemi Putri Juliantika Kusdiana (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[The Potential of Endophytic Bacteria as a Biological Controller of Leaf Fall Disease Caused by Pestalotiopsis sp. IN Rubber Plants (Hevea brasiliensis Muell. Arg.]. This study aims to explore endophytic bacteria and determine their effectiveness against the fungus Pestalotiopsis sp. which causes leaf fall on rubber plants. Pestalotiopsis sp. can attack all rubber clones resulting in decreased latex production. The presence of pathogen attacks can result in enormous economic losses. Therefore, it is very important to find an effective and efficient controlling method, one of which is through biological control of plant diseases, namely by using antagonistic microorganisms. The presence of endophytic bacteria as biological controllers has become an alternative method to reduce the practices of chemical control. This study used a Non-Factorial Completely Randomized Design (CRD) with 6 treatments and 4 replications, so that 24 experimental units were obtained, using Potato Dextrose Agar (PDA) media for the in vitro antagonist test using the dual culture method. Namely P₀ = Control, P₁ = Pestalotiopsis sp. 1 vs Bacteria P, P₂ = Pestalotiopsis sp. 2 vs Bacteria B, P₃ = Pestalotiopsis sp. 3 vs Bacteria C, P₄ = Pestalotiopsis sp. 4 vs Bacteria E, P₅ = Pestalotiopsis sp. 5 vs Bacteria F. The results indicated that antagonistic treatment of endophytic bacteria in vitro affected the percentage of inhibitory power of the mycelium of the fungus Pestalotiopsis sp. by endophytic bacteria at 1 - 6 Days After Incubation (DAI). The 3% KOH method and gram staining showed that samples P₁, P₂, P₅ did not produce mucus and were purple in colour (positive), but samples P₃, P₄, showed mucus and were pink in colour (negative). Hypersensitivity reactions to tobacco plants samples P₁, P₂, P₃, P₄, P₅ did not show negative characteristics or did not cause changes in coloration and symptoms on leaves of tobacco plant.